Comparative analysis of gut fungal composition and structure of the yaks under different feeding models - Zhu, Yanbin; Cidan, Yangji; Sun, Guangming; Li, Xin; Shahid, Muhammad Akbar; Luosang, Zhaxi; Suolang, Zhaxi; Suo, Lang; Basang, Wangdui (Frontiers in Veterinary Science, 2023)
The yaks that inhabit the Tibetan plateau are a rare breed that is closely related to local economic development and human civilization. This ancient breed may have evolved a unique gut microbiota due to the hypoxic high-altitude environment. The gut microbiota is susceptible to external factors, but research regarding the effects of different feeding models on the gut fungal community in yaks remains scarce. In this study, we compared and analyzed the composition and variability of the gut fungal community among wild yaks (WYG), house-feeding domestic yaks (HFG), and grazing domestic yaks (GYG). The results revealed that Basidiomycota and Ascomycota were the most preponderant phyla in the gut fungal community, regardless of feeding models. Although the types of dominant fungal phyla did not change, their abundances did. Intergroup analysis of fungal diversity showed that the Shannon and Simpson indices of WYG and GYG were significantly higher than those of HFG. Fungal taxonomic analysis showed that there were 20 genera (Sclerostagonospora and Didymella) that were significantly different between WYG and GYG, and 16 genera (Thelebolus and Cystobasidium) that were significantly different between the WYG and HFG. Furthermore, the proportions of 14 genera (Claussenomyces and Papiliotrema) significantly decreased, whereas the proportions of eight genera (Stropharia and Lichtheimia) significantly increased in HFG as compared to GYG. Taken together, this study indicated that the gut fungal composition and structure differ significantly between yaks raised in different breeding groups.